In vitro and in vivo Study on an Injectable Glycol Chitosan/Dibenzaldehyde-Terminated Polyethylene Glycol Hydrogel in Repairing Articular Cartilage Defects - Yang, Jianhua; Jing, Xiaoguang; Wang, Zimin; Liu, Xuejian; Zhu, Xiaofeng; Lei, Tao; Li, Xu; Guo, Weimin; Rao, Haijun; Chen, Mingxue; Luan, Kai; Sui, Xiang; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
The normal anatomical structure of articular cartilage determines its limited ability to regenerate and repair. Once damaged, it is difficult to repair it by itself . How to realize the regeneration and repair of articular cartilage has always been a big problem for clinicians and researchers . Here, we conducted a comprehensive analysis of the physical properties and cytocompatibility of hydrogels, and evaluated their feasibility as cell carriers for ADSC transplantation. Concentration-matched hydrogels were co-cultured with ADSCs to confirm ADSC growth in the hydrogel and provide data supporting in vivo experiments, which comprised the hydrogel/ADSCs, pure-hydrogel, defect-placement, and positive-control groups. Rat models of articular cartilage defect in the knee joint region was generated, and each treatment was administered on the knee joint cartilage area for each group; in the positive-control group, the joint cavity was surgically opened, without inducing a cartilage defect. The reparative effect of injectable GCS/DF-PEG hydrogel on injured articular cartilage was evaluated by measuring gross scores and histological score of knee joint articular-cartilage injury in rats after eight weeks. The 1.5% GCS/2% DF-PEG hydrogels degraded quickly in vitro. Then, We perform in vivo and in vitro experiments to evaluate the feasibility of this material for cartilage repair in vivo and in vitro.